PERBANDINGAN HASIL BELAJAR KIMIA SISWA DENGAN MODEL PROBLEM BASED LEARNING DAN THINK PAIR SHARE PADA MATERI KELARUTAN DAN HASIL KALI KELARUTAN - Gisna Wira; Nofri Yuhelman; Jumriana Rahayuningsih (Chemistry Education Department of Education and Teaching Faculty, 2019)
This study aims to determine whether there is a significant difference between student chemistry learning outcomes in the solubility material and solubility results applying the Problem Based Learning learning model and Think Pair Share learning model in the solubility material and solubility results in class XII IPA SMA Negeri 1 Pangean. This research uses a quantitative approach. This type of research is Quasi experimental research (quasi-experimental) with a design that is Posttets Only, Non Equivalent Control Group Design. The population in this study were students of class XI IPA of SMA Negeri 1 Pangean which were divided into 2 classes, namely class XI IPA 1 and XI IPA 2. The sampling technique was cluster random sampling. Data collection techniques used are observation and tests. The instrument used in this study was a test namely Posttest. The data analysis technique used is the Non-parametric Mann Whitney U Test. The results of data analysis concluded the significance value = 0.278. Because the significance is> 0.05 then Ho is accepted. So it can be concluded that there is no difference in student learning outcomes with the learning model Problem Based Learning and Think Pair Share on the solubility material and the solubility results in class XI Science in SMA Negeri 1 Pangean.